Multihormonal induction of hepatic α(2u)-globulin mRNA as measured by hybridization to complementary DNA - Kurtz, David T. (1977)
A procedure is presented for the preparation of a (3)H-labeled complementary DNA (cDNA) specific for the mRNA coding for α(2u)-globulin, a male rat liver protein under multihormonal control that represents approximately 1% of hepatic protein synthesis. Rat liver polysomes are incubated with monospecific rabbit antiserum to α(2u)-globulin, which binds to the nascent α(2u)-globulin chains on the polysomes. These antibody-polysome complexes are then adsorbed to goat antiserum to rabbit IgG that is covalently linked to p-aminobenzylcellulose. mRNA preparations are thus obtained that contain 30-40% α(2u)-globulin mRNA. A labeled cDNA is made to this α(2u)-globulin-enriched mRNA preparation by using RNA-dependent DNA polymerase (reverse transcriptase). To remove the non-α(2u)-globulin sequences, this cDNA preparation is hybridized to an RNA concentration × incubation time (R(0)t) of 1000 mol of ribonucleotide per liter × sec with female rat liver mRNA, which, though it shares the vast majority of mRNA sequences with male liver, contains no α(2u)-globulin mRNA sequences. The cDNA remaining single-stranded is isolated by hydroxylapatite chromatography and is shown to be specific for α(2u)-globulin mRNA by several criteria. Good correlation was found in all endocrine states studied between the hepatic level of α(2u)-globulin, the level of functional α(2u)-globulin mRNA as assayed in a wheat germ cell-free translational system, and the level of α(2u)-globulin mRNA sequences as measured by hybridization to the α(2u)-globulin cDNA. Thus, the hormonal control of hepatic α(2u)-globulin synthesis by sex steroids and thyroid hormone occurs through modulation of the cellular level of α(2u)-globulin mRNA sequences, presumably by hormonal control of transcriptive synthesis.